Acetyl‐11‐keto‐β‐boswellic acid ameliorates renal interstitial fibrosis via Klotho/TGF‐β/Smad signalling pathway. Issue 10 (28th July 2018) - Liu, Minna; Liu, Tianlong; Shang, Peijin; Zhang, Yikai; Liu, Limin; Liu, Ting; Sun, Shiren
Abstract: Acetyl‐11‐keto‐β‐boswellic acid (AKBA), an active triterpenoid compound from the extract of Boswellia serrate, has been reported previously in our group to alleviate fibrosis in vascular remodelling. This study aimed to elucidate the in vivo and in vitro efficacy and mechanism of AKBA in renal interstitial fibrosis. The experimental renal fibrosis was produced in C57BL/6 mice via unilateral ureteral obstruction (UUO). Hypoxia‐induced HK‐2 cells were used to imitate the pathological process of renal fibrosis in vitro. Results showed that the treatment of AKBA significantly alleviated UUO‐induced impairment of renal function and improved the renal fibrosis by decreasing the expression of TGF‐β1, α‐SMA, collagen I and collagen IV in UUO kidneys. In hypoxia‐induced HK‐2 cells, AKBA displayed remarkable cell protective effects and anti‐fibrotic properties by increasing the cell viability, decreasing the lactate dehydrogenase (LDH) release and inhibiting fibrotic factor expression. Moreover, in obstructed kidneys and HK‐2 cells, AKBA markedly down‐regulated the expression of TGFβ‐RI, TGFβ‐RII, phosphorylated‐Smad2/3 (p‐Smad2/3) and Smad4 in a dose‐dependent fashion while up‐regulated the expression of Klotho and Smad7 in the same manner. In addition, the effects of AKBA on the Klotho/TGF‐β/Smad signalling were reversed by transfecting with siRNA‐Klotho in HK‐2 cells. In conclusion, our findings provide evidence that AKBA can effectively protect kidney against interstitial fibrosis, and this renoprotective effect involves the Klotho/TGF‐β/Smad signalling pathway. Therefore, AKBA could be considered as a promising candidate drug for renal interstitial fibrosis.